Cross-Bridge Free Vascularized Fibular Graft for Reconstruction of Extensive Traumatic Tibial Defects - Tarek Abdalla El-Gammal; Amr El-Sayed; Mohamed Mostafa Kotb; Waleed Riad Saleh; Yasser Farouk Ragheb; Mohamed Mohamed Morsy; Yousif Tarek El-Gammal; Mahmoud Mohammed Saad; Omar Ahmed Refai (Journal of Reconstructive Microsurgery Open)
Background The cross-bridge free flap technique has been described for salvage of cases of traumatic lower limb defects when adequate recipient vessels in the same limb are lacking. While previous accounts mainly focused on utilizing muscle, myocutaneous, or perforator skin flaps, this study presents a series of cross-bridge free vascularized fibular transfer for reconstruction of traumatic tibial defects with extensive soft tissue loss.